Innovative Toilet Bed Safety for Bedridden in Naradhiwas Rajanagarindra Hospital - Kuiburd, Thussaneeya; Suksabay, Pornpen; Buraphan, Nikorn; Duereh, Amara; Wansawat, Tidarat (Princess of Naradhiwas University Journal, 2020)
The objectives of this research were to develop and examine the effect of Innovative Toilet Bed Safety for Bedridden in reducing the incidence of risk form conventional excretory care and to study the satisfaction of nurses and caregivers on the use of Innovative Toilet Bed Safety for Bedridden. The participants were selected by simple random sampling, comprised of thirty nurses and thirty covering of Innovative Toilet Bed Safety for Bedridden. The data were collected using research instruments including 1) the complication report 2) the incident report and 3) the questionnaire related to satisfaction of using Innovative Toilet Bed Safety for Bedridden for nurses and covering. Data were analyzed using descriptive statistics. The results found that all patients ( 100%) receiving bowel care with Innovative Toilet Bed Safety for Bedridden were no complication of the disease, normal vital signs, not falling and no humid skin. Nurses were satisfied with using of the innovative bed at the highest level in three aspects which wear economical aspect (M = 4.61, SD = .48), application (M = 4.58, SD = .53), and safety (M = 4.57, SD = .48) . The satisfaction of usefulness was high level ( M = 3.90, SD = .44) while the patients relatives were satisfied with using of the innovative bed at high level in all aspects, including safety (M = 3.00, SD = .00), application (M = 4.58, SD = .53), economical aspect (M = 2.97, SD = .13), and usefulness (M = 2.45, SD = .30) In addition, Innovative Toilet Bed Safety for Bedridden could reduce risk and increase patient safety. Nurse who provides Innovative Toilet Bed Safety for Bedridden bedside care should use to take care of patients while excretion especially Muslim patients who have to clean with water after excretion by following the spiritual dimension.